Soil pH and the Home Landscape or Garden - Amy L. Shober; Christine Wiese; Geoffrey C. Denny (EDIS)
Homeowners and gardeners alike are interested in soil pH because soil pH directly affects the growth and quality of many landscape plants by influencing the chemical form of many elements in the soil and soil microbial processes. This revised 3-page fact sheet explains soil pH and provides strategies for Master Gardeners and homeowners to make the most of the pH in the home landscape or garden. Written by Amy L. Shober, Christine Wiese, and Geoffrey C. Denny and published by the UF Department of Soil and Water Science, July 2011.